PENGARUH PENERAPAN SISTEM ENTERPRISE RESOURCE PLANNING (ERP) DAN KUALITAS SISTEM INFORMASI AKUNTANSI TERHADAP EFEKTIVITAS PENGENDALIAN INTERNAL ATAS PELAPORAN KEUANGAN PADA PT WASKITA KARYA TBK (STUDI EMPIRIS UNIT KERJA YANG BERADA DI BAWAH KANTOR DIVISI I INFRASTRUKTUR) - Farradhi, Muhammad; Evayani, Evayani (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2020)
This paper is intended to determine the application of Enterprise Resource Planning (ERP) applications and the quality of accounting information systems towards the implementation of internal control over financial reporting at PT. Waskita Tbk. The population in this study was PT Waskita Tbk employees who were under the Division I office in charge of the Sumatran region with a total population of 552 employees, with a sample used by 100 employees. Data analysis method in this study uses multiple regression analysis. The results showed that the simultaneous Corporate Resource Planning System and the quality of the accounting information system influence significant effect for the assistance of internal control over financial statements. While Enterprise System Resource Planning has a significant effect on internal control over financial reporting, accounting accounting information systems have a significant effect on controlling financial reporting. Researching to improve internal control over reporting, PT. Waskita Tbk. Continue to renew the use of information technology to be able to increase the use of internal control.